Avaliação em escala laboratorial da utilização do processo eletrolítico no tratamento de águas - Otenio, Marcelo Henrique; Panchoni, Luciana Cadioli; Cruz, Gabriela Correia Araújo da; Ravanhani, Clézio; Bidoia, Ederio Dino [UNESP] (Sociedade Brasileira de Química, 2008)
Water treatment uses chlorine for disinfection causing formation of trihalomethanes. In this work, an electrolytic water pre-treatment was studied and applied to the water from a fountainhead. The action against microorganisms was evaluated using cast-iron and aluminum electrodes. Assays were made in laboratory using the electrolytic treatment. After 5 min of electrolysis the heterotrophic bacteria count was below 500 cfu/mL and complete elimination of total and fecal coliforms was observed. Using electrolytic treatment as a pretreatment of conventional tap water treatment is proposed.
Laboratory scale assessment of an electrolytic process for water treatment
Keywords: electrolytic treatment; water disinfection; water quality